Management of Service Marketing in Increasing Customer’s Satisfaction at Madrasah Aliyah Negeri Jambi Province - Amiruddin Amiruddin; Ahmad Husein Ritonga; Samsu Samsu (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2021)
The purpose of this study was to detail the planning, coordinating, implementing, and supervising of MAN Jambi Province's marketing of services in order to increase customer satisfaction. Through participant observation, this study employs a qualitative descriptive technique. The number of participants in this study was 51. Data collection methods include observation, interviews, and documentation analysis. Data analysis, namely data reduction, data display, and conclusion drafting/ verification. Based on the findings of the research on service marketing management in raising customer happiness in MAN Jambi Province, it is possible to conclude that the planning, organization, and implementation of service marketing in raising customer satisfaction in MAN Jambi Province was successful.